Kartki na wojnę, której nie było. Planowany mechanizm reglamentacji artykułów pierwszego zapotrzebowania w PRL w wypadku sytuacji nadzwyczajnej - Zawistowski, Andrzej (Dzieje Najnowsze, 2016)
Ration Cards for a War that Never Came. Planned Mechanism of Rationing Basics in the People’s Republic of Poland in the Case of an Extraordinary Situation Twentieth–century Poland experienced four periods of rationing basics: 1915–1921 (i.e. the First World War and the Polish–Bolshevik war), 1939–1949 (World War II and the post–war period), 1951–1953 (the height of Stalinism), and 1976–1989 (the breakdown of the communist economy and years of a universal lack of commodities in shops). Against this background the fact that during the 1961 Berlin Crisis the authorities of the People’s Republic of Poland made preparations for rationing in case of an extraordinary situation remains totally unknown. The system in question was based upon the structures of the Civic Militia, but was never applied, even when conditions prevailing on the domestic market required rapid intervention and the introduction of rationing (e.g. in 1976). The article presents the system in question as well as its structure, organisation, and evolution. The author tried to solve the question why this carefully planned system and millions of printed ration cards were destroyed and never used.